Urban Microclimate Modelling for Comfort and Energy Studies 2021
DOI: 10.1007/978-3-030-65421-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Anthropocene or Urbanocene?

Abstract: We live in times of great changes. Global warming is altering the planetary thermal equilibrium, causing deep changes in our lifestyles. Economic transformations are also pushing the society toward new organisational structures, able to respond to the characters of a deeply globalised world. The human activity has an impact on the ecological system that had never been seen before. As a result, we are exposed to new risks, including extreme climatological events, pandemic diseases and massive migrations. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Microclimate exerts an influence on electrodermal activity, which in turn correlates with our physiological and mental well-being. An illustration of this association concerning human health is evident in the impact of urban microclimate on our thermal comfort [ 5 ]. However, the connections between microclimate and biological processes are intricate and frequently nonlinear.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Microclimate exerts an influence on electrodermal activity, which in turn correlates with our physiological and mental well-being. An illustration of this association concerning human health is evident in the impact of urban microclimate on our thermal comfort [ 5 ]. However, the connections between microclimate and biological processes are intricate and frequently nonlinear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, heat waves have been shown to seriously impair students’ health and productivity [ 4 ]. Palme and Salvati (2021) highlighted that there is relatively inadequate research focusing on the connections between microclimates and human health and emotions [ 5 ]. Therefore, it is crucial to delve into how microclimates influence health and productivity to tackle this overlooked issue.…”
Section: Introductionmentioning
confidence: 99%
“…As an example related to human health, microclimate in urban areas affects our thermal comfort [12]. However, the relationships between microclimate and biological processes are complex and often nonlinear.…”
Section: The Importance Of Microclimatementioning
confidence: 99%
“…Among other studies, our work was inspired by the earlier work of Palme and Salvati [12], in which they concluded that modified urban microclimates had a deep impact on the comfort of the inhabitants. Palme and Salvati lamented that while there have been various studies conducted on the effects of urbanization on the microclimate and on how the microclimate has changed human health in the efforts to redesign and restructure urban areas, there have been relatively few studies on the relationships between the microclimate and human health and emotions [12].…”
Section: Introductionmentioning
confidence: 99%
“… 5. Massimo Palme and Agnese Salvati, “Introduction: Anthropocene or Urbanocene?” in Urban Microclimate Modelling for Comfort and Energy Studies , ed. Massimo Palme and Agnese Salvati (Cham: Springer, 2021), 1-9. …”
mentioning
confidence: 99%